Knowledge Sharing Behaviour: the Effect of Psychological Safety on Balance Scorecard (BSC) Implementation - Siti Rodiah; Ertambang Nahartyo (Journal of Accounting and Investment, 2019)
This study aims to compare the influence of transformational and transactional leadership on psychological safety. In addition, it examines the effect of psychological safety on the scope of balanced scorecard (BSC) implementation through knowledge sharing behaviour. This study uses a 2 x 2 between-subjects experimental design and independent t-test to test Hypotheses 1 and 2. Hypotheses 3 and 4 use hierarchical regression. To answer the questions in this study, the researchers conducted experiments with Master of Accounting and Master of Economics Development students at the Faculty of Economics and Business, Gadjah Mada University. The results of the hypothesis testing in this study support Hypotheses 1, 2 and 3, while Hypothesis 4 is not supported because it does not meet the requirements of mediation testing.